2020
DOI: 10.1128/mbio.03236-19
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Viral Infection Alters the Gut Microbiota by Inducing Inappetence

Abstract: Respiratory viral infections are extremely common, but their impacts on the composition and function of the gut microbiota are poorly understood. We previously observed a significant change in the gut microbiota after viral lung infection. Here, we show that weight loss during respiratory syncytial virus (RSV) or influenza virus infection was due to decreased food consumption, and that the fasting of mice altered gut microbiota composition independently of infection. While the acute phase tumor necrosis factor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
118
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(133 citation statements)
references
References 57 publications
4
118
1
3
Order By: Relevance
“…Decreased production of this key cytokine along with increased viral replication, due to changes in cellular proliferation and metabolism driven by the loss of IFI44, may go some way to explaining these observations. We saw no change in tumor necrosis factor (TNF) but an increase in CD8 cells; this reflects our recent findings that TNF is associated with early weight loss after RSV infection but not later time points, whereas CD8 cells are associated with reduced food intake leading to weight loss (27).…”
Section: Discussionsupporting
confidence: 84%
“…Decreased production of this key cytokine along with increased viral replication, due to changes in cellular proliferation and metabolism driven by the loss of IFI44, may go some way to explaining these observations. We saw no change in tumor necrosis factor (TNF) but an increase in CD8 cells; this reflects our recent findings that TNF is associated with early weight loss after RSV infection but not later time points, whereas CD8 cells are associated with reduced food intake leading to weight loss (27).…”
Section: Discussionsupporting
confidence: 84%
“…Notably, opportunistic pathogens from the Bacteroides genera showed high modulation during the study, and some species positively correlated with the SARS-CoV-2 levels. This evidence can be connected with a recent study where the sphingosine gene expression was signi cantly correlated with increased Bacteroides in patients with acute respiratory viral infections 28 and gastrointestinal in ammation disorders 30 .…”
Section: Discussionsupporting
confidence: 77%
“…Studies connecting the microbiota with distal organs in regulatory functions such as gut-lung axis have revealed a key role in the respiratory system 27 . It has been reported that respiratory viral infections alter the gut microbiota, modulating the antiviral immune response through TNF-and CD8 + cells 28 . For example, gastric disorders during respiratory syncytial virus (RSV) or in uenza virus infection in mice resulted in signi cantly altered gut microbiota diversity, increased Bacteroidetes, and a concomitant decrease in Firmicutes phyla abundance.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that novel coronavirus infects intestinal epithelial cells via ACE2 receptors and transmembrane protease serine and induces proinflammatory chemokines and cytokines production, which leads to acute intestinal inflammation [52,53]. Furthermore, some reports indicate gastrointestinal symptoms such as diarrhea, as well as detection of SARS-Cov2 RNA in fecal samples of some patients affected by COVID-19 [50,54]. On the other hand, the gut microbial imbalance is associated with acute respiratory distress syndrome (ARDS) [50,55], and COVID-19 may progress to the acute ARDS [56].…”
Section: Coronavirus Disease-2019mentioning
confidence: 99%